β-Catenin signaling induces CYP1A1 expression by disrupting adherens junctions in Caco-2 human colon carcinoma cells - Kasai, Shuya; Ishigaki, Takanori; Takumi, Ryo; Kamimura, Toru; Kikuchi, Hideaki (Biochimica et biophysica acta, 2013)
The aryl hydrocarbon (Ah) receptor is one of the best known ligand-activated transcription factors. The present study has focused on the wound-healing process on Ah receptor function. Depletion of calcium from culture medium of Caco-2 human colon carcinoma cells by transfer to Minimal Essential Medium (Spinner Modification; S-MEM) destroyed adherens junctions and the cells were used as the model of wound-healing process. Calcium depletion induced both nuclear translocation of the Ah receptor, and increased expression of CYP1A1 and Slug mRNAs in Caco-2 cells. However, expression of Slug mRNA was not significantly induced by treatment with 2,3,7,8-tetrachlorodibenzo-p-dioxin. Knockdown of the Ah receptor and treatment with Ah receptor antagonists decreased level of CYP1A1 mRNA. The fragment of E-cadherin released by γ-secretase was not involved in induction of CYP1A1 mRNA following S-MEM treatment. Knockdown of β-catenin increased levels of Ah receptor mRNA, which may be attributable to direct or indirect involvement of β-catenin in suppression of the Ah receptor gene. Our results suggest that mRNA induction of some genes by destruction of adherens junctions depends on the Ah receptor. β-Catenin, one of the components of the adherens junction, was released from the E-cadherin complex, which resulted in its increased interaction with the Ah receptor, and was translocated into the nucleus, and consequently the target genes would be transcribed. Our observations suggest that some aspects of the molecular mechanism of wound healing involve the Ah receptor. ► Depletion of calcium by transfer of cells to S-MEM destroyed adherens junctions. ► Nuclear translocation of the Ah receptor induced CYP1A1 and Slug mRNAs. ► β-Catenin was released from E-cadherin complexes by destruction of adherens junctions. ► Interaction between β-catenin and the Ah receptor increased after S-MEM treatment. ► Knockdown of β-catenin increased the level of Ah receptor mRNA.